The Ecosystem of Quranic Literacy: Exploring Management Dynamics in Tartila Method - Feriska Listrianti; Wina Amalia (Al-Qalam Institue, 2025)
This study examines the learning management approach of the Tartila method in enhancing students' Qur'an reading skills, in response to the challenge of improving the effectiveness of teaching Qur'an literacy in formal institutions. This study employs a case study design, collecting data through in-depth interviews, document analysis, and field findings, which are then analyzed thematically to enhance the credibility of the findings. The results showed that the management of the Tartila method was carried out systematically through careful planning, involving the classification of students and the preparation of certified teachers. This approach included structured implementation with spiritual opening activities, core sessions that combined classical and individual learning, and concise closing. The achievement of students' fluent reading of the Qur'an is monitored through various evaluation mechanisms, ranging from daily to comprehensive final exams, with an overall success rate of 68%. The main supporting factors include teacher competence, adequate facilities, and parental support, while inhibiting factors include teacher inconsistency, student indiscipline, and lack of monitoring from parents at home. The implications of this study include strategic recommendations for the development of more adaptive Qur'anic teaching practices and educational policies, as well as identifying crucial areas for future research to optimize the effectiveness of these learning methods.